2016
DOI: 10.1097/mib.0000000000000728
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Immunochemical Test Versus Fecal Calprotectin for Prediction of Mucosal Healing in Crohnʼs Disease

Abstract: Both FIT and Fcal were correlated with the mucosal status of CD. However, the specificity of FIT was not satisfactory, particularly for small bowel lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“… 38 However, in patients with CD, faecal haemoglobin was less sensitive for reflecting CD lesions in the small bowel compared with calprotectin. 9 Likewise, in our study, we found that the diagnostic value (specificity, PPV, NPV and AUC) of faecal haemoglobin for small bowel inflammation was much lower than calprotectin or lactoferrin. These findings might suggest that FIT is more suitable for the detection of blood in the colon and rectum, and should be mainly used for screening large bowl inflammation in IBD patients.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“… 38 However, in patients with CD, faecal haemoglobin was less sensitive for reflecting CD lesions in the small bowel compared with calprotectin. 9 Likewise, in our study, we found that the diagnostic value (specificity, PPV, NPV and AUC) of faecal haemoglobin for small bowel inflammation was much lower than calprotectin or lactoferrin. These findings might suggest that FIT is more suitable for the detection of blood in the colon and rectum, and should be mainly used for screening large bowl inflammation in IBD patients.…”
Section: Discussionsupporting
confidence: 63%
“… 8 , 9 , 38 FIT has several advantages over faecal calprotectin testing in terms of user-friendliness, lower cost, simplicity, clean handling and the ability to carry out rapid assays by using an automated measurement system. 8 , 9 , 38 A direct comparison between the value of faecal calprotectin and haemoglobin indicated that both biomarkers are equally useful for the assessment of mucosal inflammation in patients with UC. 38 However, in patients with CD, faecal haemoglobin was less sensitive for reflecting CD lesions in the small bowel compared with calprotectin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations